METODE ISTINBATH DEWAN SYARIAH WAHDAH ISLAMIYAH DALAM MENETAPKAN HUKUM BPJS KESEHATAN MANDIRI - Islahuddin Ramadhan Mubarak; Sulkifli Herman; Rahmat Saputra (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
This study aimed to recognize the law of Individual Healthcare of Social Security Agency (BPJS Kesehatan Mandiri) in Islamic law by linking the fatwa of the Sharia Council of Wahdah Islamiyah regarding its legal status. This study tried to examine the flow and contract system of BPJS Kesehatan Mandiri and istinba>t method of Sharia Council of Wahdah Islamiyah in determining the law of BPJS Kesehatan Mandiri. The method in this study used qualitative research based on field research with observation, interview, and manuscript collection techniques, and descriptive analysis in summarizing research findings. The results found were as follows: First, the concept of social security prescribed in Islam to actualize ta?a>wun, tada>mun, or taka>ful is the concept of insurance conducted in a way a tabarru? agreement is there, that is a form of contract which is conducted with the aim of goodness and helping each other. Second, BPJS Kesehatan is a public legal entity that is responsible for providing social security for the entire community based on Law No. 40 of 2004 and Law No. 24 of 2011 concerning the Social Security Organizing Agenc Third, the istinba>t method of the Wahdah Islamiyah Sharia Council is based on the Qur'an, Sunna, Ijmak and Qiya>s. Fourth, the recommendations from istinba>t of Sharia Council of Wahdah Islamiyah regarding the ideas and concepts of social security are that it is not a problem, however the flow and contract system are not yet in accordance with the sharia. Fifth, the recommendations of istinba>t results of Sharia Council of Wahdah Islamiyah regarding the existence of BPJS Kesehatan are that it is needed by Indonesian people, then it is not difficult to make social insurance based on sharia rules, if this is not possible, then the community should be given a choice to choose an insurance in accordance with sharia principles.